The effect of absent or deferred antibiotic treatment on complications of common infections in primary care. (November 2022) - Dahlén, Elin; Collin, Julius; Hellman, Jenny; Norman, Christer; Nauclér, Pontus; Ternhag, Anders
Highlights: Infectious complications from upper respiratory tract infections to lower urinary tract infections are serious but rare. Antibiotics do not seem to lower this risk in cases with upper respiratory tract infections. On the contrary, the complication risk was decreased for antibiotic-treated urinary tract infection cases. Abstract: Objectives: The objective of this study was to compare the incidence rate for complications to upper respiratory tract infections (URTIs), including acute bronchitis and lower urinary tract infections (UTIs), for those treated with antibiotics compared to those who were not. Methods: This was a population-based retrospective cohort study in Sweden. Patients diagnosed with otitis, pharyngotonsillitis, sinusitis, acute bronchitis, and lower UTI in primary care between 2014 and 2020 were included. Data on prescribed and dispensed antibiotics and comorbidities for each subject were collected. The outcome we investigated was the number of infectious complications within 30 days and if antibiotic treatment had any effect on risk reduction. Results: There were 202, 995 episodes of otitis, 388, 158 pharyngotonsillitis, 125, 792 sinusitis, 220, 960 bronchitis, and 377, 954 lower UTIs in our cohort. No increased risk for complications was seen for untreated compared with treated cases with URTI. For lower UTI, the adjusted odds ratio for febrile UTI or bloodstream infection was 1.53 (95% confidence interval 1.39-1.68). Conclusion: The risk for infectious complications from common URTIs is low and not modified by antibiotic treatment. On the contrary, patients diagnosed with UTI in whom antibiotics were withheld had an increased 30 days risk for severe infections.